PEMAHAMAN MASYARAKAT TENTANG NILAI-NILAI LOCAL GENIUS DAN IMPLIKASINYA TERHADAP KETAHANAN SOSIAL BUDAYA (Studi Tentang Upacara Adat Katoba pada Suku Muna di Kabupaten Muna Propinsi Sulawesi Tenggara) - , LAODE ABDUL ALIM RAHMAD ISHAK,S.S, Prof. Dr. Kodiran, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to find out public understanding about values of local genius in katoba ceremony and its implications for social cultural resilience of Muna society. The methods used in this research is a qualitative method. Key informants in this research were 14 people consisting of 3 persons of religion, 3 persons of indigenous people, as well as 8 activists cultural observer, which is determined by purposive sampling. While regular informant amounted to 40 people that is determined by accidental sampling. The result of this research indicate that the public's understanding about the values of local genius in katoba traditional ceremony has changed. The change ultimately have implications to the social cultural of Muna society. One side, the change has been made economic benefits. But the other hand, the change finally suspected to be the major cause of social patology, as well as the threat of loss of originality of the cultral elements of Muna.